Tumor diagnosis recharacterization enabled by comprehensive genomic profiling to guide precision medicine strategy - Ann Carr; Jennifer B. Jackson; Chris Coldren; Pranil Chandra; Faezeh Koohestani; Michelle Shiller; Robert Auber (npj Precision Oncology)
Abstract Comprehensive genomic profiling (CGP) via next-generation sequencing is standard clinical practice for advanced and metastatic cancers in the U.S. and can help identify clinically actionable alterations in patients who may benefit from targeted therapies. CGP can also complement clinicopathological findings and in certain cases, may lead to diagnostic recharacterization resulting in more precise therapeutic strategies. Here, we highlight examples where molecular findings resulted in tumor re-evaluation and subsequent recharacterization. Twenty-eight cases where CGP results were inconsistent with initial pathological diagnosis and clinical presentation were selected for secondary clinicopathological review to explore alternative diagnostic explanations more consistent with the genomic results. Genomic profiling identified clinically actionable and prognostic variants leading to more accurate therapeutic recommendations based on the updated diagnoses highlighting the value of CGP beyond biomarker detection for therapy selection and supporting its complementary use in diagnostic confirmation to unveil opportunities for precision medicine strategies.